INKORPORASI PERSPEKTIF GENDER DALAM PENGEMBANGAN REKAYASA ALAT DAN MESIN PERTANIAN - NUR SUHAETI, RITA; SUHARNI SIWI, SRI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 2 Juli 2004)
Incorporation of Gender Perspective in Agricultural Machinery Engineering. Development is basically gender neutral. However, gender bias often occurs in the development implementation and it leads to gender inequity and gender inequality. This implies that only one gender side (mostly men) accesses and takes a part in the various development programs, including agricultural development. In addition, they also control and benefit its output and outcomes. In this reform era, agricultural sector still plays an important role in the Indonesia’s economy. Agribusiness and smallholders would be successful if all discrimination forms for agribusiness agent’s empowerment is eradicated and market mechanism fairness could be served. Due to cultural bias existence, roles of women in economic aspects are often taken for granted. Therefore, dissemination of Republic Indonesia’s Act No 7/1984 especially in the articles 11 and 14 to all stakeholders responsible for agricultural development implementation in various sectors at rural areas is required so that that woman would benefit from labor saving technology skill. Social and institutional constraints should be overcome, in order that woman farmers needs skill on operating and repairing simple agricultural machineries to lighten they daily drudgery.
Keywords: Incorporation of Gender Perspective, Gender Inequity and Gender Inequality